The Effect of PSD-93 Deficiency on the Expression of Early Inflammatory Cytokines Induced by Ischemic Brain Injury - Qingxiu Zhang; Hongyu Cheng; Rong Rong; Hui Yang; Qiuhong Ji; Qingjie Li; Liangqun Rong; Gang Hu; Yun Xu (Cell Biochemistry and Biophysics, 2015)

Were Plasma Trace Element Levels Changed in the Children with ADHD? - Rongwang Yang; Weijia Gao; Rong Li; Zhengyan Zhao (Biological Trace Element Research, 2015)

Characteristics of gravity anomalies and prediction of volcanosedimentary boron deposit distribution in the Xiongba area, Tibet - Li-Rong Song; Chang-Qing Yu; Gui-Hua Li; Yang-Yang Feng; Jun-Jie He (Applied Geophysics, 2015)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Angiotensin II increases secreted frizzled-related protein 5 (sFRP5) expression through AT1 receptor/Rho/ROCK1/JNK signaling in cardiomyocytes - Xin Jin; Bingyan Guo; Jie Yan; Rong Yang; Liang Chang; Yaling Wang; Chenglong Miao; Suyun Liu; Hui Zhang; Yongjun Li (Molecular and Cellular Biochemistry, 2015)

ATF6 pathway of unfolded protein response mediates advanced oxidation protein product-induced hypertrophy and epithelial-to-mesenchymal transition in HK-2 cells - Xun Tang; Xiujie Liang; Minhui Li; Tingting Guo; Na Duan; Yue Wang; Guang Rong; Lei Yang; Shaojie Zhang; Jun Zhang (Molecular and Cellular Biochemistry, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

A Real-time monitoring and early warning system for landslides in Southwest China - Neng-pan Ju; Jian Huang; Run-qiu Huang; Chao-yang He; Yan-rong Li (Journal of Mountain Science, 2015)

Purification and Antioxidant Property of Antioxidative Oligopeptide from Short-Necked Clam ( Ruditapes philippinarum ) Hydrolysate In Vitro - Rong Li; Zui-su Yang; Yu Sun; Li Li; Jia-Bin Wang; Guofang Ding (Journal of Aquatic Food Product Technology, 2015)

Application of Lactic Acid Bacteria (LAB) in freshness keeping of tilapia fillets as sashimi - Rong Cao; Qi Liu; Shengjun Chen; Xianqing Yang; Laihao Li (Journal of Ocean University of China, 2015)

The MADS ‐box transcription factor FgMcm1 regulates cell identity and fungal development in F usarium graminearum - Cui Yang; Huiquan Liu; Guotian Li; Meigang Liu; Yingzi Yun; Chenfang Wang; Zhonghua Ma; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary In eukaryotic cells, MADS ‐box genes are known to play major regulatory roles in various biological processes by combinatorial interactions with other transcription factors. In this study, we functionally characterized the FgMCM1 MADS ‐box gene in F usarium graminearum , the causal agent of wheat and barley head blight. Deletion of FgMCM1 resulted in the loss of perithecium production and phialide formation. The F gmcm1 mutant was significantly reduced in virulence, deoxynivalenol biosynthesis and conidiation. In yeast two‐hybrid assays, FgMcm1 interacted with M at1‐1‐1 and F st12, two transcription factors important for sexual reproduction. Whereas F gmcm1 mutants were unstable and produced stunted subcultures, F gmcm1 mat1‐1‐1 but not F gmcm1 fst12 double mutants were stable. Furthermore, spontaneous suppressor mutations occurred frequently in stunted subcultures to recover growth rate. Ribonucleic acid sequencing analysis indicated that a number of sexual reproduction‐related genes were upregulated in stunted subcultures compared with the F gmcm1 mutant, which was downregulated in the expression of genes involved in pathogenesis, secondary metabolism and conidiation. We also showed that culture instability was not observed in the F vmcm1 mutants of the heterothallic F usarium verticillioides . Overall, our data indicate that FgMcm1 plays a critical role in the regulation of cell identity, sexual and asexual reproduction, secondary metabolism and pathogenesis in F . graminearum .

SKF-96365 strongly inhibits voltage-gated sodium current in rat ventricular myocytes - Kui-Hao Chen; Hui Liu; Lei Yang; Man-Wen Jin; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2015)

The role of Cyclin G1 in cellular proliferation and apoptosis of human epithelial ovarian cancer - Lifei Jiang; Rong Liu; Yingying Wang; Chunmiao Li; Qinghua Xi; Jianxin Zhong; Jian Liu; Shuyun Yang; Juan Wang; Menghui Huang; Chunhui Tang; Zheng Fang (Journal of Molecular Histology, 2015)

Phosphorylation of p38 MAPK mediates aquaporin 9 expression in rat brains during permanent focal cerebral ischaemia - Xiaoyu Wei; Xuxia Ren; Rong Jiang; Hui Li; Fei Gao; Yuqin Chen; Jiaojiao Hou; Xueyuan Liu; Shanquan Sun; Mei Yang (Journal of Molecular Histology, 2015)

Establishment and characterization of a novel cell line from midgut tissue of Helicoverpa armigera (Lepidoptera: Noctuidae) - Jianghuai Li; Fei He; Yongbo Yang; Yutao Xiao; Rong Peng; Hanchao Yao; Xianchun Li; Jianxin Peng; Huazhu Hong; Kaiyu Liu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Dissipation and Degradation Dynamics of Thifluzamide in Rice Field - Li Na Wei; Ping Wu; Fu Rong Wang; Hong Yang (Water, Air, & Soil Pollution, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Immune protective effect of human alpha-1-antitrypsin gene during β cell transplantation in diabetic mice - Lu Yang; Yu-Ting Liao; Xiao-Fei Yang; Li-Wei Reng; Hui Qi; Fu-Rong Li (Immunologic Research, 2015)

Polycyclic aromatic hydrocarbons associated with total suspended particles and surface soils in Kunming, China: distribution, possible sources, and cancer risks - Xiaoxia Yang; Dong Ren; Wenwen Sun; Xiaoman Li; Bin Huang; Rong Chen; Chan Lin; Xuejun Pan (Environmental Science and Pollution Research, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Modification and simulation of Rhizomucor miehei lipase: the influence of surficial electrostatic interaction on enantioselectivity - Gang Xu; Xiao Meng; Lin-Jie Xu; Li Guo; Jian-Ping Wu; Li-Rong Yang (Biotechnology Letters, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

Soil cellulase activity and fungal community responses to wetland degradation in the Zoige Plateau, China - Li-sha Wu; Su Feng; Yuan-yang Nie; Jian-hong Zhou; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2015)

Introducing a salt bridge into the lipase of Stenotrophomonas maltophilia results in a very large increase in thermal stability - Jian-Ping Wu; Mu Li; Yong Zhou; Li-Rong Yang; Gang Xu (Biotechnology Letters, 2015)

Over-expression of SlWRKY39 leads to enhanced resistance to multiple stress factors in tomato - Xiao-chun Sun; Yong-feng Gao; Hui-rong Li; Shu-zhang Yang; Yong-sheng Liu (Journal of Plant Biology, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)